The role of acidification in the inhibition of Neisseria gonorrhoeae by vaginal lactobacilli during anaerobic growth - Wade Jeremy J; Graver Michelle A (BMC, 2011)
Abstract Background Vaginal lactobacilli protect the female genital tract by producing lactic acid, bacteriocins, hydrogen peroxide or a local immune response. In bacterial vaginosis, normal lactobacilli are replaced by an anaerobic flora and this may increase susceptibility to Neisseria gonorrhoeae, a facultative anaerobe. Bacterial interference between vaginal lactobacilli and N. gonorrhoeae has not been studied in liquid medium under anaerobic conditions. By co-cultivating N. gonorrhoeae in the presence of lactobacilli we sought to identify the relative contributions of acidification and hydrogen peroxide production to any growth inhibition of N. gonorrhoeae. Methods Three strains of N. gonorrhoeae distinguishable by auxotyping were grown in the presence of high concentrations (107-108 cfu/mL) of three vaginal lactobacilli (L. crispatus, L. gasseri and L. jensenii) in an anerobic liquid medium with and without 2-(N-morpholino)-ethanesulfonic (MES) buffer. Fusobacterium nucleatum was used as an indicator of anaerobiosis. Bacterial counts were performed at 15, 20 and 25 h; at 25 h pH and hydrogen peroxide concentrations were measured. Results Growth of F. nucleatum to >108 cfu/mL at 25 h confirmed anaerobiosis. All bacteria grew in the anaerobic liquid medium and the addition of MES buffer had negligible effect on growth. L. crispatus and L. gasseri produced significant acidification and a corresponding reduction in growth of N. gonorrhoeae. This inhibition was abrogated by the addition of MES. L. jensenii produced less acidification and did not inhibit N. gonorrhoeae. Hydrogen peroxide was not detected in any experiment. Conclusions During anaerobic growth, inhibition of N. gonorrhoeae by the vaginal lactobacilli tested was primarily due to acidification and abrogated by the presence of a buffer. There was no evidence of a specific mechanism of inhibition other than acid production under these conditions and, in particular, hydrogen peroxide was not produced. The acidification potential of vaginal lactobacilli under anaerobic conditions may be their most important characteristic conferring protection against N. gonorrhoeae infection.